The Effect of Digital Marketing and Media Promotion Utilization to a Bakpia Patok Yogyakarta SMES’ Sales Performance - Marissa Grace Haque (Program Pascasarjana Universitas Negeri Makassar, 2020)
This study aims to determine the effect of digital marketing and the use of media promotion on its sales performance of one of Bakpia Patok SMEs in Yogyakarta. The method used is explanatory research, and statistical analysis with regression test, correlation, determination, and hypothesis test. Results of this digital marketing study has a significant effect on sales performance 41,8 percent, Hypothesis testing is obtained by t arithmetic > t table or (8,208 > 1,986). The use of promotional media has a significant effect on sales performance 43,2 percent, Hypothesis testing is obtained by t arithmetic > t table or (8,457 > 1,986). Digital marketing and the use of promotional media simultaneously have a significant effect on sales performance with the regression equation Y = 9,672 + 0,362X1 + 0,405X2 and contribute with as much influence as 52,4 percent, Hypothesis testing is obtained by F-count > F table or (51,264 > 2,700).